ANALISIS EFISIENSI PEMASARAN BUAH NAGA (Studi Kasus di Desa Paiton Kecamatan Paiton Kabupaten Probolinggo) - syamsudin syamsudin (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
ABSTRACK The purpose of this study is. 1) To find out the dragon fruit marketing channel and find out the marketing efficiency of dragon fruit. The location of the study was done intentionally in Paiton Village. Random sampling method for farmers and to determine respondents to marketing institutions using snow ball sampling. Data analysis method used price transmission elasticity and direct approach. The results of this study indicate that, in Paiton Village there are two marketing channels. From the two existing marketing channels it turns out that the most efficient marketing channel is marketing channel I. This is indicated by the share received by farmers at 76.4,%. With a marketing margin of Rp. 3,500 To π / c on channel I which is 3,9. Whereas on channel II the share of farmers is 70.1% with a marketing margin of Rp. 4,375 for n / c on channel II at middleman level 4.0 and at the retail level of 2.8.